Pengembangan Media Pembelajaran Berbasis Motion Graphics untuk Edukasi Kesiapsiagaan Tsunami dengan Metode ADDIE - Susanto, Agus; Annas Setiawan Prabowo; Sriadji, Rubino (P3M Politeknik Negeri Cilacap, 2026)
Indonesia is geographically located in the Pacific Ring of Fire, making it a country with a high risk of natural disasters, especially tsunamis. Cilacap Regency, as one of the disaster-prone areas, has a low level of preparedness, thus requiring increased public knowledge about disaster risks. This study aims to improve the preparedness of educational units in facing tsunami disasters through educational media based on motion graphics animation. The method used is the development of ADDIE, which has five stages: Analysis, Design, Development, Implementation, and Evaluation, which is designed to increase understanding and awareness of the importance of disaster mitigation. The results of this study are an increase in students' response abilities in facing emergency situations, as evidenced by the average score of students' pre-test of 58.4, increasing to 82.6 in the post-test. The increase in the score of 24.2 points resulted in an N-Gain value of 0.58, which is in the moderate category, indicating that the use of educational animation media based on motion graphics is effective in increasing tsunami preparedness. Thus, this technology-based educational approach can be an innovative solution in supporting the Disaster Safe Education Unit (SPAB) program and creating a more disaster-resilient society.